Combining ancestral sequence reconstruction with protein design to identify an interface hotspot in a key metabolic enzyme complex. Issue 2 (5th January 2017) - Holinski, Alexandra; Heyn, Kristina; Merkl, Rainer; Sterner, Reinhard
ABSTRACT: It is important to identify hotspot residues that determine protein–protein interactions in interfaces of macromolecular complexes. We have applied a combination of ancestral sequence reconstruction and protein design to identify hotspots within imidazole glycerol phosphate synthase (ImGPS). ImGPS is a key metabolic enzyme complex, which links histidine and de novo purine biosynthesis and consists of the cyclase subunit HisF and the glutaminase subunit HisH. Initial fluorescence titration experiments showed that HisH from Zymomonas mobilis (zmHisH) binds with high affinity to the reconstructed HisF from the last universal common ancestor (LUCA‐HisF) but not to HisF from Pyrobaculum arsenaticum (paHisF), which differ by 103 residues. Subsequent titration experiments with a reconstructed evolutionary intermediate linking LUCA‐HisF and paHisF and inspection of the subunit interface of a contemporary ImGPS allowed us to narrow down the differences crucial for zmHisH binding to nine amino acids of HisF. Homology modeling and in silico mutagenesis studies suggested that at most two of these nine HisF residues are crucial for zmHisH binding. These computational results were verified by experimental site‐directed mutagenesis, which finally enabled us to pinpoint a single amino acid residue in HisF that is decisive for high‐affinity binding of zmHisH. Our work shows that the identification of protein interface hotspots can be very efficient when reconstructed proteins with different binding properties are included in the analysis. Proteins 2017; 85:312–321. © 2016 Wiley Periodicals, Inc.